Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil - Carvalho, Adeilma Nascimento De; Oliveira, Aníbal Ramadan; Argolo, Poliane Sá; Ferragut, Francisco (Zootaxa, 2017)
During a survey of predatory mites on cocoa cropping areas in Bahia State, north-eastern Brazil, three undescribed species of Phytoseiidae were collected on natural vegetation associated with crops. Typhlodromips baculiductus n. sp., Graminaseius bahiensis n. sp. and Typhlodromalus annulatus n. sp. are described and diagnosed. Comments on the boundary between the genera Amblydromalus Chant & McMurtry and Typhlodromalus Muma are also included.